Assessment of Consumer Satisfaction with Health Care Services in Community Pharmacies in Sierra-Leone - Margret Olubunmi Afolabi; Kanayo Patrick Osemene (University of Huddersfield Press, 2021)
This study examined community pharmacy healthcare services accessed by consumers; determined their level of satisfaction with such healthcare services; and assessed the relationship between consumers' level ofsatisfaction and consumers' demographic characteristics. A cross sectional survey of 583 participants was conducted using a pretested self-administered questionnaire presented in a 5-point Likert scale. Descriptive and parametric techniques were used to summarize data at P< 0.05. Mean age of consumers was 35.2years ± 5.39 SD. Services most sought after were patients counseling (87.8%), purchase of prescription and non-prescription medicines (82%), purchase of non-drug products (74.1%) and treatment of minor ailments (71%). Services least sought after were screening services (5.3%), health education (4.6%), monitoring device (4.5%), and sexuality education (3.6%). About (84.8%) of participants reported they had good satisfaction. Moderate satisfaction was 50.4 %, and poor satisfaction was 38%. Their degree of satisfaction was significantly associated with age (p=.031), gender (p=.012) education (p=.016) and occupation (p=004). Satisfaction-related statements that had good scores were: information provided by pharmacists, and quality of drugs. Moderate scores were rate of service delivery, insufficient stock. Statements with poor scores were unavailability of pharmacists in their work place, inadequate hospitality of pharmacy staff, and prices of medicines.